Neuregulin 1 improves complex 2-mediated mitochondrial respiration in skeletal muscle of healthy and diabetic mice - Gaël Ennequin (Nature Portfolio, 2017)
Abstract It has been reported that neuregulin1 (NRG1) improves glucose tolerance in healthy and diabetic rodents. In vitro studies also suggest that NRG1 regulates myocyte oxidative capacity. To confirm this observation in vivo, we evaluated the effect on mitochondrial function of an 8-week treatment with NRG1 in db/db diabetic mice and C57BL/6JRJ healthy controls. NRG1 treatment improved complex 2-mediated mitochondrial respiration in the gastrocnemius of both control and diabetic mice and increased mitochondrial complex 2 subunit content by 2-fold. This effect was not associated with an increase in mitochondrial biogenesis markers. Enhanced ERBB4 phosphorylation could mediate NRG1 effects on mitochondrial function through signalling pathways, independently of ERK1/2, AKT or AMPK.